Institutional Analysis of â€œGapoktanâ€ In the Protected Forest Management Unit Area of North Kota Agung in Tanggamus Regency of Lampung Province - Aminah, Lina Nur; Safe'i, Rahmat; Febryano, Indra Gumay (Journal of Sylva Indonesiana, 2018)
The Forest Management Unit (FMU) is the area unit of forest management which its area has been set up with clear boundaries, it has been the predominant covered by forests, it has been managed for long term including their was an explicit objective which declared in the forest management plan. FMU IX is a part of FMU area which is located in North Kota Agung. It has obtained processing area permit through CF program (CFM). CFM managed by Gapoktan (Association of Farmers Groups) who has obtained management area license. Good or bad of the CFM depends on the farmers who are incorporated in â€œGapoktanâ€ therefore research on the role of this institution is needed. This study aimed: 1) to analyze the institutional system in two Gapoktan, namely Beringin Jaya and Sinar Mulya in the boundary of CFM land in FMU IX areas of North Kota Agung, and 2) to evaluate the level of effectiveness of â€œGapoktanâ€ organization. Appeal data have been developed by the method of SSBP (situation-structure-behavior-performance). The results showed the different performance of both Gapoktan . Beringin Jaya has had good institutional situation, its organizational structure was running well, its member behavior was active in every activities, and performance was very good. Meanwhile in Sinar Mulya, its organizational structure was not going well, the activities were lack hence its performance was not satisfied. The result of the effectiveness level at Beringin Jaya was effective, on the other hand the effectiveness level at Sinar Mulya was quite effective.